PKM TATA KELOLA PEMBERIAN MAKANAN TAMBAHAN (PMT) PADA SEKOLAH PAUD BKB KEMAS LESTARI - Sembiring, Evi Dora; Anggriawan, Muhammad Angga; Handayani, Novi; Pertiwi, Sari Putri; Samsinar, Ade (Batara Wisnu : Indonesian Journal of Community Services, 2023)
BKB Kemas Lestari PAUD School is located at Blok F 14C No.2 RT.04/RW25 Komp. TBL Kel, Unyur, Kec. Serang, Serang City, Banten 42111. This school is located in a residential area of ??the Taman Banten Lestari housing complex which has around 30 students. This early childhood school implements a 5-day school program, Monday-Friday, with learning methods according to children’s interests, talents and growth and development. Every second and fourth Sunday of each month, Supplementary Feeding (PMT) activities are carried out which aim to improve nutrition and health and optimize children’s physical growth according to health standards. This article is a form of Community Service Output (PKM) which aims to explain and describe the management of providing additional food (PMT) at the BKB Kemas Lestari PAUD school. The research method used was by directly participating in PMT activities, namely in preparing food menus, equipment to be used and attending when students enjoyed food as well as reviewing the program budget and accountability. The results of this research are that the PMT program carried out by the BKB Kemas Lestari early childhood school already has good governance because it is carried out jointly by the school and parents/guardians of students, is scheduled and has a separate fixed budget